2015
DOI: 10.5539/ijbm.v10n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Linking Sustainability to Quality Management and Firm Performance

Abstract: Environmental management practices have evolved significantly over the past two decades. During that time, sustainable operations management practices have purportedly made positive contributions to overall firm performance. This paper develops two conceptual frameworks regarding the relationships among specific elements of environmental management, quality management, and firm performance. We suggest that innovation in quality management mediates the relationship between design for environment and firm perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
1
5
0
3
Order By: Relevance
“…Acredita-se que em empresas agroindustriais a sustentabilidade deve ser o principal item de inovações organizacionais e tecnológicas para se gerar retornos tanto de receita, quanto sociais e ambientais, sendo este o tripé da sustentabilidade (Elkington, 1994;Mishra & Napier, 2015;Nguyen, Phan, & Matsui, 2018), pois, ser uma empresa ambientalmente correta diminui os custos, visto que se acabam reduzindo os insumos que se utilizam. Deste modo, o processo passa a gerar receitas adicionais com produtos melhores e/ou permite A gestão da qualidade é considerada adequada como suporte para a integração de considerações de sustentabilidade em áreas como o desenvolvimento de produtos.…”
Section: Qualidade E Sustentabilidadeunclassified
See 1 more Smart Citation
“…Acredita-se que em empresas agroindustriais a sustentabilidade deve ser o principal item de inovações organizacionais e tecnológicas para se gerar retornos tanto de receita, quanto sociais e ambientais, sendo este o tripé da sustentabilidade (Elkington, 1994;Mishra & Napier, 2015;Nguyen, Phan, & Matsui, 2018), pois, ser uma empresa ambientalmente correta diminui os custos, visto que se acabam reduzindo os insumos que se utilizam. Deste modo, o processo passa a gerar receitas adicionais com produtos melhores e/ou permite A gestão da qualidade é considerada adequada como suporte para a integração de considerações de sustentabilidade em áreas como o desenvolvimento de produtos.…”
Section: Qualidade E Sustentabilidadeunclassified
“…A sustentabilidade pode ser definida como o design, gestão e melhoria dos processos de negócios de uma empresa para impactar positivamente a sociedade, o desempenho econômico da empresa e o ambiente físico. Sob essa visão, torna-se importante incorporar práticas ambientalmente responsáveis em todos os aspectos do gerenciamento de operações (Mishra & Napier, 2015).…”
Section: Qualidade E Sustentabilidadeunclassified
“…Some of the studies conducted by Waddock & Graves (t.t. ), Preston & O'Bannon (1997), Münstermann et al (2010), Urban & Naidoo (2012), Aggarwal (2013), Utami & Ryadi (2013) and Mishra & Napier (2015) concluded that business performance influences business continuity. It means that with the existence of good business performance, it can guarantee business continuity.…”
Section: Application Of the Right Model To Maintain And Improve The Smentioning
confidence: 99%
“…The business continuity of the food industry is largely determined by business performance. This is based on the results of Münstermann, Eckhardt, & Weitzel, (2010), Urban & Naidoo (2012), Aggarwal (2013), Utami & Ryadi (2013) and Mishra & Napier (2015). However, the business performance of the food industry in Southeast Sulawesi Province also declined, which was marked by a decline in the value of production.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper special emphasis is placed on supply chain CSR as this is the focus of many firms' current sustainability efforts. Sustainability is defined in a process-centric way as the design, management, and improvement of a company's business processes to positively impact society, the economic performance of the firm, and the environment (Mishra & Napier, 2015). Sustainability goes beyond Corporate Social Responsibility in being self-perpetuating (sustainable as the name implies) rather than a program adopted because of external demands on the firm and not necessarily a permanent, continuously improving one.…”
Section: Introductionmentioning
confidence: 99%